A high-purity porous boron carbide ceramic for nuclear control rods and a preparation method thereof

Through the use of polyethylene glycol -butb butthalodethyls and elenetelotide binders and large -particle -size boron carbide powder during the preparation of porous boronized boronized ceramics, and for oxidation and sintering and sintering, the density of porous boron ceramics is solved. It is difficult to improve and manufacture high costs, and realize the high -pore rate, uniform hole structure and good mechanical properties.

CN118930271BActive Publication Date: 2025-01-28YANTAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411124474.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-01-28
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The prior art has problems such as difficult to improve density, high manufacturing cost, uneven pore structure and large number of closed pores when preparing porous boron carbide ceramics, which affects its performance in high-temperature air-cooled reactor core control rods.

Method used

By mixed with polyethylene glycolinaldehyde -butyl and ethyl acet buttate, mixes with large -particle -size boron carbide powder after mixing with large -particle -size boron powder and sintering and sintering, forming a boron carbide ceramics with high pore rate and uniform pore structure.

Benefits of technology

Boronized boronized ceramics with high purity, low density, uniform hole structure and good mechanical properties are suitable for the nuclear control stick of high -temperature gas and cold stacks, reducing the cost of manufacturing and improving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118930271B_ABST
    Figure CN118930271B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramic preparation, and specifically relates to a high-purity porous boron carbide ceramic for a nuclear control rod and a preparation method thereof. The first semi-finished product with high porosity and strength is obtained by oxidation sintering, and then a phenolic resin is introduced into the first semi-finished product as a carbon source, and the boron carbide ceramic is obtained by first-stage and second-stage reaction sintering. The boron carbide ceramic has the advantages of easy process control, low energy consumption, low cost, high production capacity, high yield rate and stable finished product performance, and is very suitable for large-scale production; the boron carbide ceramic has the advantages of pure phase, high porosity, uniform pore structure, good and stable mechanical properties, and is suitable for nuclear control rods of high-temperature gas-cooled reactors, especially has a high opening rate, which is conducive to the discharge of helium from the nuclear control rod, thereby ensuring the safe use of the nuclear control rod.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic preparation, and in particular relates to a high-purity porous boron carbide ceramic for a nuclear control rod and a preparation method thereof. Background Art

[0002] In the field of nuclear energy, boron carbide ceramics are often used to prepare control rods for nuclear reactors because the boron isotope B10 has the characteristics of high neutron absorption cross-section, wide absorption energy spectrum, low price, abundant raw material sources, no strong secondary radiation after absorbing neutrons, and easy waste disposal.

[0003] Since the sintering difficulty of boron carbide ceramics is very high, in order to improve the density of boron carbide ceramics, higher molding pressure and sintering temperature are usually used. Compared with dense boron carbide ceramics, the preparation difficulty of porous boron carbide ceramics is greater. This is because the porous boron carbide ceramic green body adopts a lower molding pressure, and the green body contains a large amount of pore-forming agent, which makes the boron carbide particles in the green body not in close contact. In order to improve the mechanical properties of the prepared porous boron carbide ceramics, more sintering aids are often added to the green body. Therefore, the porous boron carbide ceramics prepared by the prior art generally have the problem of high content of other phases.

[0004] Patent CN 201910042944.8 discloses "a method for preparing porous boron carbide ceramics for high-temperature gas-cooled reactor nuclear control rods". This method introduces boron carbide whiskers and boron nitride into the raw materials so that the prepared boron carbide ceramics have good mechanical properties while having a certain porosity. However, the use of expensive boron carbide whiskers and micron-sized boron carbide powder in this method will increase the manufacturing cost, and the introduction of boron nitride will reduce the total carbon and boron content of the porous boron carbide ceramics. In addition, due to the small particle size of the boron carbide powder, a large number of closed pores are present in the prepared porous boron carbide ceramics. When the boron carbide ceramics are used as nuclear control rods for high-temperature gas-cooled reactors, helium gathers in the closed pores, which has a more serious destructive effect on the swelling of the control rods. Summary of the invention

[0005] In order to solve the problems raised by the background technology, the present invention provides a high-purity porous boron carbide ceramic for nuclear control rods and a preparation method thereof.

[0006] The technical solution of the present invention is as follows:

[0007] The present invention provides a high-purity porous boron carbide ceramic for nuclear control rods, wherein the total content of carbon and boron in the boron carbide ceramic is 98.5% to 99.8%, and the density is 1.63 to 1.93 g / cm 3 The total porosity is 23.4% to 35.3%, the open pores account for 98.7% to 98.9% of the total pores, the compressive strength is 379 to 583 MPa, and the fracture toughness is 3.1 to 3.8 MPa·m 1 / 2 .

[0008] Boron carbide ceramics have a uniform porous structure, the boron carbide particles have no sharp edges, and there is a smooth transition between the particles.

[0009] The present invention also provides a method for preparing the high-purity porous boron carbide ceramic for nuclear control rods, comprising the following steps:

[0010] (1) mixing polyvinyl butyral and n-butyl acetate to obtain a binder;

[0011] (2) mixing boron carbide powder with a binder, and pressing and molding the mixture to obtain a green body;

[0012] (3) placing the green body in an air atmosphere and performing oxidation sintering to obtain a first semi-finished product;

[0013] (4) the first semi-finished product is impregnated with an ethanol solution of a phenolic resin and then dried to obtain a second semi-finished product;

[0014] (5) The second semi-finished product is placed in an inert atmosphere, subjected to a first-stage reaction sintering, and then heated to undergo a second-stage reaction sintering to obtain a boron carbide ceramic.

[0015] In the step (1), the weight ratio of polyvinyl butyral to n-butyl acetate is 1:1.2-1.5;

[0016] In the step (2), the particle size of the boron carbide powder is 50 to 100 μm; the weight ratio of the boron carbide powder to the binder is 1:0.06 to 0.09;

[0017] In the step (5), the first stage of reaction sintering is carried out at a temperature of 690-720° C. and a time of 20-30 min; the second stage of reaction sintering is carried out at a temperature of 2120-2180° C. and a time of 90-120 min.

[0018] In the step (1), the weight ratio of polyvinyl butyral to n-butyl acetate is 1:1.2;

[0019] In the step (2), the particle size of the boron carbide powder is 100 μm; the weight ratio of the boron carbide powder to the binder is 1:0.06;

[0020] In the step (5), the first stage of reaction sintering is carried out at a temperature of 690° C. and a time of 30 minutes; the second stage of reaction sintering is carried out at a temperature of 2180° C. and a time of 90 minutes.

[0021] In the step (2), the pressure of the pressing molding is 30 to 50 MPa.

[0022] In the step (3), the temperature of the oxidation sintering is 860-890° C. and the time is 25-40 minutes.

[0023] In the step (4), the concentration of the ethanol solution of the phenolic resin is 17 to 25 g / L.

[0024] The immersion in step (4) is specifically, immersing at a negative pressure of -0.04 to -0.07 MPa for 12 to 18 minutes, and then immersing at normal pressure for 6 to 9 minutes;

[0025] In the step (4), the drying temperature is 60 to 90° C. and the drying time is 20 to 50 minutes.

[0026] Beneficial Effects

[0027] (1) The boron carbide ceramic provided by the present invention has the advantages of pure phase, high porosity, uniform pore structure, good and stable mechanical properties, and is suitable for nuclear control rods of high-temperature gas-cooled reactors. In particular, it has a high open porosity, which is conducive to the discharge of helium from the nuclear control rods, thereby ensuring the safe use of the nuclear control rods.

[0028] (2) The present invention first obtains a first semi-finished product with high porosity and strength through oxidation sintering, then introduces phenolic resin as a carbon source into the first semi-finished product, and obtains boron carbide ceramics through first-stage and second-stage reaction sintering. Except for an oxidation sintering furnace and a reaction sintering furnace, the present invention does not require high requirements for other production equipment. The present invention has the advantages of easy process control, low energy consumption, low cost, high production capacity, high yield rate, and stable finished product performance, and is very suitable for large-scale production.

[0029] (3) The binder formed by mixing polyvinyl butyral and n-butyl acetate in the present invention is a viscous fluid, which has a good bonding effect on boron carbide powder, can make the green body have higher strength, avoid damage to the green body during molding, and improve the yield rate of the green body.

[0030] (4) The present invention uses large-particle boron carbide powder as raw material, which can form larger pores between the boron carbide particles, which can improve the porosity of the finished product on the one hand, and reduce the difficulty of impregnating the first semi-finished product with an ethanol solution of phenolic resin on the other hand.

[0031] (5) After the boron carbide powder and the binder are uniformly mixed, the present invention has good plasticity and no pores, which can avoid the generation of pore defects in the subsequent blank and improve the uniformity of the pore structure of the finished product.

[0032] (6) The present invention adopts oxidation sintering, which, on the one hand, removes polyvinyl butyral and n-butyl acetate in the green body; on the other hand, forms a boron oxide film layer on the surface of the boron carbide particles, and uses molten boron oxide to bond the boron carbide particles together during sintering, so that the first semi-finished product has a higher strength, so as to ensure that the first semi-finished product maintains a complete shape in subsequent operations. In addition, the higher the temperature of the oxidation sintering and the longer the sintering time, the more boron oxide is generated, and the higher the strength of the corresponding first semi-finished product is, and the process is easy to control.

[0033] (7) The present invention introduces phenolic resin into the first semi-finished product to provide a carbon source for the reduction reaction of boron oxide in the subsequent reaction sintering.

[0034] (8) The present invention adjusts the impregnation amount of the phenolic resin by changing the concentration of the ethanol solution of the phenolic resin and the pressure of the impregnation process according to the boron oxide content in the first semi-finished product, so that the boron carbide ceramic does not contain boron oxide and the residual carbon content is as small as possible, further realizing easy control of the process.

[0035] (9) The present invention heat treats the second semi-finished product at a relatively low temperature so that the phenolic resin is fully cracked into carbon to ensure that the subsequent second-stage reaction sintering can fully react. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a microscopic photograph of the boron carbide ceramic prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The following examples are intended to illustrate the present invention rather than to further limit the present invention.

[0038] The present invention provides a high-purity porous boron carbide ceramic for nuclear control rods, wherein the total content of carbon and boron in the boron carbide ceramic is 98.5% to 99.8%, and the density is 1.63 to 1.93 g / cm 3 The total porosity is 23.4% to 35.3%, the ratio of open pores to total pores is 98.7% to 98.9%, the compressive strength is 379 to 583 MPa, and the fracture toughness is 3.1 to 3.8 MPa·m 1 / 2 .

[0039] The pores in the boron carbide ceramic include open pores and closed pores, and the sum of their porosities is the total porosity.

[0040] Boron carbide ceramics have a uniform porous structure, the boron carbide particles have no sharp edges, and there is a smooth transition between the particles.

[0041] The boron carbide ceramic provided by the present invention has the advantages of pure phase, high porosity, uniform pore structure, good and stable mechanical properties, and is suitable for nuclear control rods of high-temperature gas-cooled reactors. In particular, it has a very high open porosity, which is conducive to the discharge of helium from the nuclear control rods, thereby ensuring the safe use of the nuclear control rods.

[0042] In order to make the preparation process of boron carbide ceramics easy to control, low in cost and high in yield, the present invention also provides a method for preparing the high-purity porous boron carbide ceramics for nuclear control rods, comprising the following steps:

[0043] (1) Polyvinyl butyral and n-butyl acetate are mixed to obtain a binder.

[0044] The binder mixed with polyvinyl butyral and n-butyl acetate in the present invention is a viscous fluid, which has a good bonding effect on boron carbide powder, can make the green body have higher strength, avoid the green body from being damaged during molding, and improve the yield rate of the green body.

[0045] Preferably, in step (1), the weight ratio of polyvinyl butyral to n-butyl acetate is 1:1.2 to 1.5; most preferably, the weight ratio of polyvinyl butyral to n-butyl acetate is 1:1.2.

[0046] (2) After the boron carbide powder is mixed with the binder, it is pressed into a shape to obtain a green body.

[0047] Preferably, in step (2), the particle size of the boron carbide powder is 50-100 μm; the weight ratio of the boron carbide powder to the binder is 1:0.06-0.09; most preferably, the particle size of the boron carbide powder is 100 μm; the weight ratio of the boron carbide powder to the binder is 1:0.06.

[0048] The invention uses large-diameter boron carbide powder as raw material, and aims to form larger pores between boron carbide particles, which can improve the porosity of the finished product and reduce the difficulty of impregnating the first semi-finished product with an ethanol solution of phenolic resin.

[0049] After the boron carbide powder and the binder are uniformly mixed, the present invention has good plasticity and no pores, thereby avoiding the generation of pore defects in the subsequent blank and improving the uniformity of the pore structure of the finished product.

[0050] Preferably, in step (2), the pressure of the pressing molding is 30 to 50 MPa.

[0051] (3) placing the green body in an air atmosphere and performing oxidation sintering to obtain a first semi-finished product;

[0052] The present invention adopts oxidation sintering, one of the purposes is to remove polyvinyl butyral and n-butyl acetate in the green body; the second purpose is to generate a boron oxide film layer on the surface of the boron carbide particles, and to bond the boron carbide particles together by using molten boron oxide during sintering, so that the first semi-finished product has a higher strength, so as to ensure that the first semi-finished product maintains a complete shape in subsequent operations. In addition, the higher the temperature of oxidation sintering and the longer the sintering time, the more boron oxide is generated, and the higher the strength of the corresponding first semi-finished product.

[0053] Preferably, in step (3), the temperature of the oxidative sintering is 860-890° C., and the time is 25-40 min.

[0054] (4) the first semi-finished product is impregnated with an ethanol solution of a phenolic resin and then dried to obtain a second semi-finished product;

[0055] The purpose of introducing the phenolic resin into the first semi-finished product of the present invention is to provide a carbon source for the reduction reaction of boron oxide in the subsequent reaction sintering.

[0056] Preferably, in step (4), the concentration of the ethanol solution of phenolic resin is 17-25 g / L.

[0057] Furthermore, the immersion in step (4) is specifically, immersing at a negative pressure of -0.04 to -0.07 MPa for 12 to 18 minutes, and then immersing at normal pressure for 6 to 9 minutes;

[0058] In the step (4), the drying temperature is 60 to 90° C. and the drying time is 20 to 50 minutes.

[0059] According to the boron oxide content in the first semi-finished product, the concentration of the phenolic resin ethanol solution and the pressure of the impregnation process are changed to adjust the impregnation amount of the phenolic resin, so that the boron carbide ceramic does not contain boron oxide and the residual carbon content is as small as possible.

[0060] (5) The second semi-finished product is placed in an inert atmosphere, such as an argon atmosphere, and subjected to a first-stage reaction sintering. The temperature is then raised to conduct a second-stage reaction sintering to obtain a boron carbide ceramic.

[0061] Preferably, the first stage reaction sintering has a temperature of 690-720°C and a time of 20-30 minutes; most preferably, the temperature is 690°C and the time is 30 minutes. The second semi-finished product is heat treated at a relatively low temperature, the purpose of which is to fully crack the phenolic resin into carbon to ensure that the subsequent second stage reaction sintering can fully react.

[0062] Furthermore, to ensure that the boron carbide ceramic has excellent performance, in the step (5), the second stage reaction sintering has a temperature of 2120-2180°C and a time of 90-120 min; most preferably, the temperature is 2180°C and the time is 90 min.

[0063] The present invention firstly performs oxidation sintering to obtain a first semi-finished product with high porosity and strength, then introduces phenolic resin as a carbon source into the first semi-finished product, and performs first-stage and second-stage reaction sintering to obtain boron carbide ceramics. Except for an oxidation sintering furnace and a reaction sintering furnace, the present invention has low requirements on other production equipment, has the advantages of easy process control, low energy consumption, low cost, high production capacity, high yield rate, and stable finished product performance, and is very suitable for large-scale production.

[0064] The obtained boron carbide ceramic is subjected to outer circle and end surface grinding to obtain a porous boron carbide ceramic round rod, which is then placed in a stainless steel cladding, which is then packaged to assemble a nuclear control rod.

[0065] Example 1

[0066] (1) mixing polyvinyl butyral and n-butyl acetate in a weight ratio of 1:1.3 to obtain a binder;

[0067] (2) mixing boron carbide powder with a particle size of 80 μm and a binder in a weight ratio of 1:0.07, and pressing at 40 MPa to obtain a green body;

[0068] (3) placing the green body in an air atmosphere and oxidizing and sintering at 880° C. for 30 min to obtain a first semi-finished product;

[0069] (4) the first semi-finished product was immersed in an ethanol solution of phenolic resin with a concentration of 20 g / L at a negative pressure of -0.06 MPa for 14 min, then immersed at normal pressure for 8 min, and then dried at 70° C. for 40 min to obtain a second semi-finished product;

[0070] (5) The second semi-finished product is placed in an argon atmosphere, heated to 700° C. and maintained for 27 min to perform a first stage reaction sintering, and then heated to 2160° C. and maintained for 100 min to perform a second stage reaction sintering to obtain boron carbide ceramics.

[0071] Example 2

[0072] (1) mixing polyvinyl butyral and n-butyl acetate in a weight ratio of 1:1.2 to obtain a binder;

[0073] (2) mixing boron carbide powder with a particle size of 100 μm and a binder in a weight ratio of 1:0.06, and pressing at 30 MPa to obtain a green body;

[0074] (3) placing the green body in an air atmosphere and oxidizing and sintering at 890° C. for 25 min to obtain a first semi-finished product;

[0075] (4) the first semi-finished product was immersed in an ethanol solution of phenolic resin with a concentration of 17 g / L at a negative pressure of -0.07 MPa for 12 min, then immersed at normal pressure for 9 min, and then dried at 60° C. for 50 min to obtain a second semi-finished product;

[0076] (5) The second semi-finished product is placed in an argon atmosphere, heated to 690° C. and maintained for 30 min to perform a first stage reaction sintering, and then heated to 2180° C. and maintained for 90 min to perform a second stage reaction sintering to obtain a boron carbide ceramic.

[0077] Example 3

[0078] (1) mixing polyvinyl butyral and n-butyl acetate in a weight ratio of 1:1.4 to obtain a binder;

[0079] (2) mixing boron carbide powder with a particle size of 60 μm and a binder in a weight ratio of 1:0.08, and pressing at 40 MPa to obtain a green body;

[0080] (3) placing the green body in an air atmosphere and oxidizing and sintering at 870° C. for 35 min to obtain a first semi-finished product;

[0081] (4) the first semi-finished product was immersed in an ethanol solution of phenolic resin with a concentration of 23 g / L at a negative pressure of -0.05 MPa for 16 min, then immersed at normal pressure for 7 min, and then dried at 80° C. for 30 min to obtain a second semi-finished product;

[0082] (5) The second semi-finished product is placed in an argon atmosphere, heated to 710° C. and maintained for 23 min for the first stage reaction sintering, and then heated to 2140° C. and maintained for 110 min for the second stage reaction sintering to obtain boron carbide ceramics.

[0083] Example 4

[0084] (1) mixing polyvinyl butyral and n-butyl acetate in a weight ratio of 1:1.5 to obtain a binder;

[0085] (2) mixing boron carbide powder with a particle size of 50 μm and a binder in a weight ratio of 1:0.09, and pressing at 50 MPa to obtain a green body;

[0086] (3) placing the green body in an air atmosphere and oxidizingly sintering it at 860° C. for 40 min to obtain a first semi-finished product;

[0087] (4) the first semi-finished product is immersed in an ethanol solution of phenolic resin with a concentration of 25 g / L at a negative pressure of -0.04 MPa for 18 min, then immersed at normal pressure for 6 min, and then dried at 90° C. for 20 min to obtain a second semi-finished product;

[0088] (5) The second semi-finished product is placed in an argon atmosphere, heated to 720° C. and maintained for 20 min to perform a first stage reaction sintering, and then heated to 2120° C. and maintained for 120 min to perform a second stage reaction sintering to obtain a boron carbide ceramic.

[0089] Experimental Results

[0090] 1. Morphology Analysis

[0091] The boron carbide ceramics prepared in Example 1 were subjected to morphological testing. Figure 1 shown.

[0092] Boron carbide ceramics have a uniform porous structure. Boron carbide particles have no sharp edges and corners. The particles are not in point contact with a very small contact area, but in a smooth transition with a large contact area. This structure is conducive to making boron carbide ceramics have higher mechanical properties.

[0093] 2. Performance Analysis

[0094] The density, total porosity, compressive strength, fracture toughness, carbon content, and boron content of the boron carbide ceramics of Examples 1-4 were tested, and three examples in the patent application number CN 201910042944.8 (a method for preparing porous boron carbide ceramics for nuclear control rods of high temperature gas-cooled reactors) were used as comparative examples 1-3 for comparison. See Table 1 for details.

[0095] Table 1 Comparison of comprehensive properties of boron carbide ceramics

[0096]

[0097] As shown in Table 1, in terms of physical properties, the total porosity and density of the boron carbide ceramics prepared in Examples 1 to 4 are 23.4% to 35.3% and 1.63 to 1.93 g / cm 3 The total porosity and density of the boron carbide ceramics prepared in Comparative Examples 1 to 3 are 10.7% to 17.5% and 2.08 to 2.25 g / cm 3 , it is obvious that Examples 1 to 4 are lighter. In addition, the ratio of openings to total pores in Examples 1 to 4 and Comparative Examples 5 to 7 is 98.7% to 98.9% and ≥50%, respectively. Since the higher the opening ratio of the nuclear control rod for a high temperature gas-cooled reactor, the more conducive it is to the discharge of helium and the better the safety of the control rod, from this point of view, Examples 1 to 4 are better.

[0098] In terms of mechanical properties, the compressive strength and fracture toughness of the boron carbide ceramics prepared in Examples 1 to 4 are 379 to 583 MPa and 3.1 to 3.8 MPa·m, respectively. 1 / 2 The compressive strength and fracture toughness of the boron carbide ceramics prepared in Examples 1 to 3 are 634 to 705 MPa and 3.9 to 4.3 MPa·m 1 / 2 , the mechanical properties of Examples 1 to 3 have certain advantages. From the perspective that mechanical properties are inversely proportional to porosity, since the total porosity of Examples 1 to 4 is higher, the corresponding mechanical properties are naturally lower.

[0099] In terms of purity, the total carbon and boron contents of Examples 1 to 4 and Comparative Examples 1 to 3 are 99.8% and ≥98%, respectively. Obviously, considering that the higher the purity of the nuclear control rod, the higher the shielding efficiency against neutrons, Examples 1 to 4 are slightly better.

[0100] In addition, the larger the particle size of boron carbide powder, the fewer the number of pores distributed between the boron carbide particles. As the number of pores decreases, the porosity of boron carbide ceramics decreases and the density increases, which in turn leads to improved mechanical properties of boron carbide ceramics. As shown in Table 1, as the particle size of boron carbide powder increases from 50μm to 100μm, the porosity of boron carbide ceramics increases from 23.4% to 35.3%, and the density increases from 1.93g / cm 3 Down to 1.63g / cm 3 The compressive strength dropped from 583MPa to 379MPa, and the fracture toughness dropped from 3.8MPa·m 1 / 2 Reduced to 3.1MPa·m 1 / 2 This also means that: for the preparation method of the present invention, the physical and mechanical properties of boron carbide ceramics can be effectively adjusted by changing the particle size of the boron carbide powder, which has the advantage of easy process control.

[0101] In terms of sintering cost, the sintering temperatures of Examples 1 to 4 and Comparative Examples 1 to 3 are 2120 to 2180° C. and 2090 to 2140° C. respectively, which is not much different. Since Examples 1 to 4 use large-particle boron carbide powder as raw material and do not add expensive boron carbide whiskers, it helps to reduce manufacturing costs.

Claims

1. A high-purity porous boron carbide ceramic for nuclear control rods, characterized in that: The boron carbide ceramic has a total carbon and boron content of 98.5% to 99.8% and a density of 1.63 to 1.93 g / cm 3 The total porosity is 23.4%~35.3%, the open pores account for 98.7%~98.9% of the total pores, the compressive strength is 379~583 MPa, and the fracture toughness is 3.1~3.8 MPa·m 1 / 2 ; The boron carbide ceramic is prepared by the following steps: (1) mixing polyvinyl butyral and n-butyl acetate to obtain a binder; (2) After the boron carbide powder is mixed with the binder, it is pressed into a shape to obtain a green body; (3) placing the green body in an air atmosphere and performing oxidation sintering to obtain a first semi-finished product; The temperature of oxidation sintering is 860~890℃ and the time is 25~40min; (4) The first semi-finished product is impregnated with an ethanol solution of a phenolic resin and then dried to obtain a second semi-finished product; (5) The second semi-finished product is placed in an inert atmosphere, subjected to a first-stage reaction sintering, and then heated to undergo a second-stage reaction sintering to obtain a boron carbide ceramic; The first stage of reaction sintering is at a temperature of 690~720°C and a time of 20~30min; the second stage of reaction sintering is at a temperature of 2120~2180°C and a time of 90~120min.

2. The high-purity porous boron carbide ceramic for nuclear control rods according to claim 1, characterized in that: Boron carbide ceramics have a uniform porous structure, the boron carbide particles have no sharp edges, and there is a smooth transition between the particles.

3. The high-purity porous boron carbide ceramic for nuclear control rods according to claim 1, characterized in that: In the step (1), the weight ratio of polyvinyl butyral to n-butyl acetate is 1:1.2-1.5; In the step (2), the particle size of the boron carbide powder is 50-100 μm; and the weight ratio of the boron carbide powder to the binder is 1:0.06-0.

09.

4. The high-purity porous boron carbide ceramic for nuclear control rods according to claim 3, characterized in that: In the step (1), the weight ratio of polyvinyl butyral to n-butyl acetate is 1:1.2; In the step (2), the particle size of the boron carbide powder is 100 μm; the weight ratio of the boron carbide powder to the binder is 1:0.06; In the step (5), the first stage of reaction sintering is carried out at a temperature of 690°C for 30 minutes; the second stage of reaction sintering is carried out at a temperature of 2180°C for 90 minutes.

5. The high-purity porous boron carbide ceramic for nuclear control rods according to claim 1, characterized in that: In the step (2), the pressure of the pressing molding is 30-50 MPa.

6. The high-purity porous boron carbide ceramic for nuclear control rods according to claim 1, characterized in that: In the step (4), the concentration of the ethanol solution of the phenolic resin is 17-25 g / L.

7. The high-purity porous boron carbide ceramic for nuclear control rods according to claim 1, characterized in that: The immersion in step (4) is specifically, immersing at a negative pressure of -0.04 to -0.07 MPa for 12 to 18 minutes, and then immersing at normal pressure for 6 to 9 minutes; In the step (4), the drying temperature is 60-90° C. and the drying time is 20-50 min.

Citation Information

Patent Citations

  • A method for preparing boron carbide porous ceramics for nuclear control rods in high-temperature gas-cooled reactors

    CN109704771B

  • Porous boron carbide pellets prodn. - by mixing carbide powder with resin binder, compressing and heating to carbonise the resin, used in nuclear reactors

    FR2503695A1